Securing IoMT Systems via Probabilistic Trust-Epistemic Logic - Sultan, Khalid (2025)
This paper introduces a novel probabilistic logic of trust and knowledge developed to formally assess the security of the Internet of Medical Things (IoMT) applications under uncertainty. This logic enables reasoning not only about trust between devices and agents, but also about their knowledge states and the interplay between trust and knowledge in dynamic, partially observable environments. To support formal analysis, a rich set of reasoning postulates have been devised to capture how trust and knowledge interact in IoMT systems, providing a principled foundation for secure decision-making. The semantics and syntax of the trust and knowledge modalities are also defined. A verification procedure tailored to this logic and implementation using the PRISM model checker are also described. Our framework is validated through a real-world Remote Patient Monitoring (RPM) case study, demonstrating its expressive power and practical effectiveness. The results show that reasoning about trust and knowledge together can enhance the interpretability, robustness, and security of IoMT systems in a formal and automated manner.